SOSIOLOGI DALAM ADMINISTRASI BISNIS - Prof Damsar (JIAGANIS, 2016)
Abstract : This article discusses on sociology in business administration. Sociology is a scientific study on society and its social interaction, therefore, sociology take also account phenomena which occurs in the business administration. Relation between sociology and business administration take places in the overlapping subject matter, but it is not likely that sociology take over business administration (or the opposite).    Keywords: sociology, business administration, sociology of business administration